Cosmodel: an interaction model for social network games (2011)
Social network games (videogames for online social networks), have become very popular among videogame developers.Nevertheless, the conceptual aids for designers and developers of this type of games are scarce, particularly the aids that focus on interactionbetween players. Due to this, CosModel is proposed as a model for the design of social network games. CosModel is made up of three interaction design views that aid in the construction of these games and focus on enhancing player interactions. One of these views features the use of a metaphor as a conceptual aid for the design of social network games. This paper presents the theoretical background that supportsthe model, the model's development procedure and structure, and a proposed process for its implementation.